A 3D Imaging-based Critique of Wire Arc Additive Manufacturing (WAAM) Simulations - Oraby, Omar (AUC Knowledge Fountain, 2024)
Residual stresses play a critical role in the mechanical behavior and structural integrity of engineered components. Understanding and quantifying these stresses are essential for ensuring the reliable performance and durability of materials and structures. Traditionally destructive methods are used that involve sample sectioning and material removal. However, non-destructive methods have gained popularity due to their advantages in preserving the specimen's integrity for further testing and material waste reduction. Among these techniques, Digital Image Correlation (DIC) stands out as a powerful non-contact and full-field measurement approach. DIC captures displacements and strain distributions by analyzing the deformation of speckle patterns on the sample surface. It enables the extraction of residual stresses without damaging the specimen. Despite its advantages, current DIC methods primarily focus on 2D images, limiting the ability to capture the full strain field in complex 3D geometries. In this study, a novel in-situ and non-destructive methodology for measurements of residual stresses in Wire Arc Additive Manufacturing (WAAM) components using three-dimensional imaging is proposed. The methodology involves utilizing non-rigid registration to map the 3D scanned mesh of the deformed component onto a CAD template representing the undeformed component. By aligning the two surfaces, the residual strains that arise during the additive manufacturing process are captured. The measured residual stresses were compared to the results of WAAM simulation and benchmarked against process characteristics. The results demonstrated a remarkable agreement between the measured displacements and the simulations, confirming the robustness and accuracy of the proposed technique. Additionally, the measured residual stresses were shown to be significantly lower than its FE simulation counterpart. This was attributed to the fact that the depositions were separated from the substrate and thus exist in an unclamped state, which is expected to have lower stress values. Finally, the procedure was repeated for a deposition with higher heat input which yielded larger residual stresses. This showed the potential of the proposed methodology for providing an in-situ and quick feedback optimization of WAAM process parameters.